On A Curious Linear Relationship Between Rainfall Averages (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
Empirical evidence points to the fact that the area average rain rate and the fraction of the area. where rain rate exceeds a gi ven threshold tend to be highly correlated, provided the area is large enough and the threshold is chosen optimally as to increase the correlation. This fact has an important application in rainfall estimation from space using satellite borne instruillents. A statistical explanation is provided for the observed linearity, and a IIlct.hod for optimal thresholds is discussed.